THE SPATIAL MEANING IN "GADIS KRETEK" MOVIE AS A REPRESENTATION OF JAVANESE SOCIETY - Julita, Ing; Oktarina, Freta (MODUL, 2024)
The movie series "Gadis Kretek" is an adaptation of Ratih Kumala's novel, framing the family business life within the clove cigarette, known as kretek, industry. This adaptation portrays the societal realities against the background of local wisdom related to the kretek industry in Java. The kretek industry has evolved into one of the largest revenue-generating sectors for the Indonesian government, second only to oil and gas. Kretek have become a cultural heritage of Indonesia, embodying historical and cultural values intertwined with the activities of its people. These values shape a space that relates to form, function, and meaning in architecture, understood through dialogue and image within the movie's scenes. This study will analyze and interpret the production of space in the "Gadis Kretek" movie series and examine the underlying meanings as representation of Javanese society.